ECONOMIC DIVERSIFICATION: AN INSIGHT INTO SUSTAINABLE AND INCLUSIVE AGRICULTURE WITH SPECIAL REFERENCE TO PAKISTAN - Dixit P. (Russian Journal of Agricultural and Socio-Economic Sciences, 2019)
Crop diversification is an important step to deal with the challenges of present and future faced today by agriculture economies. Population explosion in agriculture economies surpassed carrying capacity of resources so endangering inclusion. Our research on economic diversification and government reform measure particularly in agriculture is to deal with sustainability of agriculture economy like Pakistan. The main objective of this paper is to analyze how economic diversification and land reform can prove to be a milestone in tackling the challenges faced by agriculture economy. In order to perform numerical and qualitative analysis of primary and secondary data, the analysis is shown through the SPSS Software. As a result, it was known that through diversification and land reforms, Pakistan's agricultural economy will be strengthened. At the end of the paper, some effective suggestion regarding inclusive agriculture model have been given, which will be important in achieving the said objectives.